Average Fracture Energy for Crack Propagation in Postfire Concrete - Kequan Yu; Jiangtao Yu; Zhoudao Lu (Advances in Materials Science and Engineering)
Wedge-splitting tests of postfire concrete specimens were carried out in the present research to obtain the load-displacement curves. Ten temperatures varying from room temperature to 600°C were employed. In order to calculate the accurate fracture energy, the tails of load-displacement curves were best fitted using exponential and power functions. Three fracture energy quantities (fracture energy GF, stable fracture energy GFS, and unstable fracture energy GFU) with their variation tendency and their mutual relationship were determined to predict energy consumption for the complete fracture propagation. Additionally, the stable fracture work WFS was also calculated. All these fracture parameters sustain an increase-decrease tendency which means that the fracture property of postfire concrete shares the same tendency.